Mechanical And Thermal Properties Of Nanoparticles Filled Silicone Rubber Composites - Kong , Siew Mui (2012)
In the first stage of current study, three types of nano fillers which are boron nitride (BN), silicon nitride (SN) and nanodiamond (ND) have been used to fabricate silicone rubber composites. Among the three fillers studied, ND has emerged as the best filler in enhancing the thermal conductivity, tensile strength and strain at break of silicone rubber composites. Therefore, ND was chosen as filler in the next stage of research. In the second stage, hybrid filler composites were fabricated by combining same type of filler with different sizes and shapes at different filler ratio. The fillers are nanodiamonds (NDs) which denoted as ND (4-15 nm), ND1 (100 nm) and ND2 (200nm). ND exhibits spherical shape while ND1 and ND2 exhibit irregular shape. All the testing results showed that hybrid ND/ND2 composite presented better performance in thermal conductivity, thermal stability and tensile strength than hybrid ND/ND1 composites. In the third stage, different loading of multiwalled carbon nanotubes (MWCNT) also added into the hybrid ND/ND2 composites at filler ratio of 1/3. Incorporation of 0.5 vol. % of MWCNT into ND/ND2 composites has increased 19 % thermal conductivity of hybrid fillers composites. Moreover, addition of MWCNT also increased the dielectric constant of ND/ND2 composites significantly. However, the dielectric loss of hybrid MWCNT/ND/ND2 composites is high at the filler loading of 0.5 vol. % to 1.0 vol. % which is not suitable to be applied as thermal interface material (TIM). The effects of MWCNT on thermal stability and tensile properties are small and negligible. Therefore, the best combination of hybrid composite in this study that can be applied as TIM in microelectronic field is 0.25 vol. % of MWCNT filled ND/ND2 composites.